PEMBERDAYAAN POTENSI LOKAL MELALUI PENGEMBANGAN WISATA HALAL: PENGABDIAN DI DESA CIKANDE - Jujun Junaedi; Dadin Solihin; Devi Eri Sandi; Nani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2026)
Cikande Village in Saguling District, West Bandung Regency, has strong natural and Islamic cultural potential to be developed as a halal tourist destination. However, low public understanding and limited infrastructure are the main obstacles. This community service aims to encourage the development of halal tourism based on local potential as an effort to improve the sustainable economy. The method used is Participatory Action Research (PAR) through observation, interviews, socialisation, training, and the formulation of strategies with the community. The results of the activity show that before the program, the community did not understand the concept of halal tourism as a whole. After the program was implemented, there was an increase in awareness, halal MSME training, and community-based tourism development planning. The community is starting to be actively involved in digital promotion and planning of halal tourism supporting facilities. This program is the first step in strengthening collaboration between the community, village government, and universities in realising Cikande Village as an inclusive and sustainable halal tourism destination.